Genetic Power of a Brazilian Three-Generation Family with Generalized Agressive Periodontitis. II (2011)
ABSTRACT: The genetic power of a Brazilian three-generation family with generalized aggressive periodontitis (GAgP) has been reported. The empirical logarithms of the odds (LOD) score thresholds for genetic linkage analysis of complex diseases proposed by Haines rely on confirmation from independent datasets. This study estimated the power of another large Brazilian family with GAgP for future linkage analysis. The three-generation family was seen at the Dental School of the Federal University of Bahia. Following the previously described methodology, full-mouth periodontal probing at 6 sites/tooth was performed in all 19 family members. Six out of 12 siblings were affected with GAgP. All affected family members were non-smokers and did not present diabetes or any other systemic condition or consanguinity. A parametric simulation (?=0) was performed on 100 replicates using the statistical software SLINK for linkage analysis. There was maximum expected LOD scores of 3.75 and 3.45 at penetrance rate F=0.98, and both studied phenocopy rates P=0.0 and P=0.02, respectively. The power of the study increased with the increase of the adopted penetrance rates in both studied phenocopy rates. The studied Brazilian three-generation family showed statistical power for future genetic linkage analysis of candidate genes to GAgP.